Term Limits for Political Party Chairpersons as an Instrument of Intra-Party Democracy: A Fiqh Siyasah Perspective - Fachrul Naufal; Muhammad Ramadhan (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
This study examines the absence of explicit term limits for political party chairpersons in Indonesia and its implications for internal party democracy. Although Article 23 paragraph (1) of Law No. 2 of 2011 on Political Parties grants political parties autonomy to regulate leadership succession through their Articles of Association and Bylaws, it does not provide minimum standards regarding leadership tenure, periodization, or elite circulation. This study employs normative legal research using statutory, case, conceptual, and fiqh siyasah approaches. The primary legal materials include the 1945 Constitution of the Republic of Indonesia, Law No. 2 of 2008 as amended by Law No. 2 of 2011, Constitutional Court Decision No. 69/PUU-XXI/2023, and relevant internal party regulations. This study finds that the absence of minimum standards for chairperson tenure may weaken leadership regeneration, reinforce the personalization of party leadership, and enable elite domination within political parties. It argues that term limits for political party chairpersons should be regulated in the Political Party Law as a minimum standard of internal democracy, while technical mechanisms concerning nomination, election, dismissal, and deliberative forums should remain within each party’s internal rules. A five-year term renewable only once is proposed as a proportional model that balances party autonomy and internal democratic accountability. From a fiqh siyasah perspective, term limitation is justified as an ethical-normative instrument to preserve amānah, promote shūrā, uphold justice, realize public benefit, and prevent istibdād in political party governance.